Argument-Driven Inquiry Model in Chemistry Learning: A Systematic Review - Siti Dzakiya Romadhoni; Sri Atun; Azlan Kamari (Universitas Syiah Kuala, 2025)
Argument driven inquiry (ADI) model is an instructional learning model that combines argumentation with inquiry-based learning. The ADI model allows students to argue actively in the learning process. Previous research studies have found that the ADI model is widely applied in the field of chemistry. This study aims to systematically synthesize research acles related to the ADI model that focus on independent and dependent variables, chemical concepts, and conclusions in chemistry learning. This study uses the systematic literature review (SLR) method for 22 articles from the google scholar, ERIC (education resources information center) and scopus databases in the period 2016- 2025. Search through relevant keyword patterns, namely